CHARACTERISTICS OF DEMINERALIZED GELATIN FROM LIZARDFISH (Saurida spp.) SCALES USING NaOH-NaCl SOLUTION - Wardhani, Dyah H; Rahmawati, Esti; Arifin, Ghozi Tsany; Cahyono, Heri (Universitas Negeri Semarang, 2017)
Demineralization is required to reduce the ash content of gelatin. Previous studies have confirmed the high quality of gelatin was produced after demineralized using combination of NaCl and aqueous NaOH. The purpose of this study was to determine the effect of NaCl on the properties of gelatin from Lizardfish (Saurida spp.) scales. The cleaned scales was demineralized using a mixture of NaOH 0.5% and NaCl (0- 0.8%), at various temperatures (45, 65, 86oC) and time (30, 60, 90 and 150 minutes). The obtained samples was determined by ash content, pH, the lightness and moisture content. Addition of NaCl reduced the ash, pH and moisture content but increased the whiteness. Gelatin physical properties increased inline with NaCl concentration. Extended demineralized period gave a positive effect on ash, pH and moisture content but opposite effect was observed in the lightness and physical properties. Extended demineralization periods in high temperature reduced gelatin quality. The highest gel strength was found at demineralization for 150 min at 65oC using a combination of NaOH 0.5% and NaCl 0.8%. At this condition, the gelatin has 10%, 1,7%, 248 bloom, and 7,1 cP of moisture content, ash, gel strength and viscosity, respectively, which fulfil SNI 06.3735.1995.